Web Application for the Best Teacher Decision Making System Using the AHP Method at SMA Al-Binaa Bekasi : Aplikasi Web untuk Pengambilan Keputusan Guru Terbaik Sistem Menggunakan Metode AHP di SMA Al-Binaa Bekasi - Moch Taufik Irfan; Andi Moch Januriana (SYSTEMATICS, 2021)
Elementary school level education, junior high school, high school is the main work of teachers, schools are very interested in maintaining the quality of teachers in the teaching and learningprocess. The process of selecting the best teachers that have been regulated in the guidelines foroutstanding teachers and goals, among others, is to increase the motivation, dedication, loyalty andprofessionalism of teachers, which is expected to have a positive effect on improving education at theschool level to the national level. In the teacher's guideline with achievement and referring to theteacher's criteria, it must refer to Pedagogic Competence, (2) Professional Competence, (3) PersonalCompetence, (4) Social Competence. SMA IT ALBINAA currently does not have a process to maintainteacher quality, so to overcome this, form a Forum Group Discussion (FGD) SMA IT ALBINAA tostandardize the criteria for selecting the best teachers in the hope of motivating teachers to be evenbetter. After that, an information system is designed which is presented by building a decision supportsystem using the Analytical Hierarchy Process (AHP) method as a method that can process data fromthe criteria that have been disclosed in the Forum Group Discussion (FGD) including Attendance,Discipline, RPP, Education Level, Number of hours teach. After that, the system will providerecommendations for the best teacher level at SMA IT ALBINAA based on the calculation of theAnalytical Hierarchy Process (AHP) followed by the final stage of testing with the Black Box testingmethod.